E0689 Echocardiographic characteristics of left ventricular noncompaction with papillary muscles involvement. (17th November 2010) - Lan, Jiang; Mingxing, Xie; Xinfang, Wang; Li, Yuan; Xiaofang, Lu; Lin, Li
Abstract : Objective: To assess the ultrasonic characteristics of the left ventricular noncompaction with papillary muscles involvement. Methods: We reviewed the echocardiographic findings in eight patients having left ventricular noncompaction with papillary muscles involvement at our hospital. We performed transthoracic echocardiography including standard parasternal (short and long axis), apical (two-chamber, three-chamber and four-chamber), and nonstandard parasternal views for all these patients. The left ventricular segments involved in noncompaction, the mitral papilary muscles and the mitral valve were the key observation. When the transthoracic echocardiography of four patients were not satisfactory, contrast echocardiography was used. Results: In all 8 patients (5 of them with severe mitral regurgitation, two with hypertrophic cardiomyopathy), the myocardium of the left ventricular segments involved in noncompaction were consist of two layers: a thin, compacted epicardial and an extremely thickened endocardial layer with prominent trabeculations and deep recesses, mitral papillary muscles involved in whole or in part, the myocardium of the papillary muscles looked like moth-eaten, appearance of blood flow from the ventricular cavity into the intertrabecular recesses both in the noncompaction myocardium and papillary muscles as visualised by colour Doppler imaging. With contrast enhancement in four of eight patients, the left ventricular endocardial borders were clearly outlined, and contrast microbubbles filled into the intertrabecular recesses both in the noncompaction myocardium and papillary muscles. Conclusion: The left ventricular noncompaction may involve the mitral papillary muscles. Transthoracic echocardiography provides definitive images of the abnormal mitral papillary muscles.